Pengaruh Kompetensi Karyawan, Motivasi Kerja, Komitmen Organisasi, Kemampuan Teknik Personal Terhadap Kinerja Sistem Informasi Akuntansi - Krisnawati, Ni Putu Ayu; Suartana, I Wayan (E-Jurnal Akuntansi; Vol 21 No 3 (2017), 2017)
Computer-based accounting information system is very important applied in Bank Perkreditan Rakyat to produce information in the form of relevant and reliable financial statements. This study aims to prove empirically the influence of Employee Competence, Work Motivation, Organizational Commitment and Personal Technical Ability to Accounting Information System Performance . The theory used in this research is the theory of justice and motivation theory. The research conducted at Rural Banks in Tabanan District.  The population of this research is 24 Rural Banks in Tabanan District. The sample used in this research is saturated sampling method. A questionnaire that returned and deserve to be processed as many as 120 questionnaires. The data analysis technique used is multiple linear regression analysis technique. The result of the research shows that the variable of Employee Competence, Work Motivation, Organizational Commitment and Personal Engineering Ability have a positive effect on Accounting Information System Performance. It means the higher the competence of employees with the system used then the perfomance of accounting information system the better.  The greater the motivation of work then the perfomance of the system used the better. The higher the support of the organization’s commitment the higher the perfomance of the accounting information system. The higher the ability of personal techniques the higher the perfomance of accounting information system. For further research is expected to develop the same research with different topics and consider other variables to determine Employee Competence, Work Motivation, Organizational Commitment and Personal Engineering Ability. For the company is expected to be a consideration to improve Employee Competence, Work Motivation, Organizational Commitment and Personal Engineering Capability which will impact on Accounting Information System Performance.